Feather‐based measures of stable isotopes and corticosterone reveal a relationship between trophic position and physiology in a pelagic seabird over a 153‐year period. (23rd December 2014) - Fairhurst, Graham D.; Bond, Alexander L.; Hobson, Keith A.; Ronconi, Robert A.
Abstract : Diet during the non‐breeding period influences condition and subsequent reproduction. Physiological mechanisms underlying such carry‐over effects are poorly understood but could be clarified by studying physiological responses to variation in diet during non‐breeding. The hormone corticosterone provides a functional link between diet and survival and reproduction, but methodological limitations have prevented previous studies from testing the hypothesis that, on an individual level, avian corticosterone levels during the non‐breeding period reflect broader patterns in feeding ecology during that time. Using museum specimens (1859–2002) and live birds (2012), we found that corticosterone from feathers (CORTf ) is negatively related to trophic position (TP) inferred from feather stable‐nitrogen isotope values ( δ 15 N) in Leach's Storm‐petrels Oceanodroma leucorhoa . CORTf was not related to stable‐carbon isotope values ( δ 13 C). We detected no temporal trends in CORTf or δ 15 N, and neither was related to a large‐scale index of winter climate, suggesting a general ecological phenomenon rather than a reflection of historical environmental changes. However, we detected a temporal trend in feather δ 13 C, and δ 13 C was related to δ 15 N. Our findings suggest a physiological benefit of feeding at higher TPs, either through increased nutritional value or reduced foraging costs associated with higher TP prey, and future research should aim to distinguish between these two explanations. Nevertheless, ours is the first evidence of a correlation between individual endocrine levels and foraging ecology, and demonstrates non‐lethal variation in a physiological mediator in turn related to variation in resource use.